Level of integration of mobile device technology in teaching and learning in universities in Botswana - Rudhumbu, Norman; Dziva, Daimond; Plessis, Elize (International journal of education and development using information and communication technology, 2021)
The study investigated the level of integration of mobile device technology in teaching and learning in Botswana universities. Botswana is one of the few African countries with a strong and stable economy and a high prevalence of technological gadgets that include mobile phones, tablets, and laptops, among others, in use in the population. Despite the prevalence of these technological gadgets, not much is known about the level of integration of technology in teaching and learning in universities in Botswana. A quantitative approach that employed a structured questionnaire for data collection was used in a study that included a sample of 360 lecturers from five out of eight selected universities in Botswana. The results of the study showed that negative attitudes of lecturers towards the integration of technology continue to be one of the major contributory factors in the low levels of technology integration in teaching and learning in universities in Botswana. The study also revealed that high Internet costs, as well as slow Internet connectivity are some of the main challenges contributing to the slow pace of technology integration in universities in Botswana. Results further showed that despite the high prevalence of mobile devices, desktops remain the main technological gadgets used during teaching and learning at universities in Botswana.